Parametric Study of Tuned Mass Dampers for Long Span Transmission Tower-Line System under Wind Loads - Li Tian; Yujie Zeng (Shock and Vibration)
A parametric study of tuned mass dampers for a long span transmission tower-line system under wind loads is done in this paper. A three-dimensional finite element model of transmission tower-line system is established by SAP2000 software to numerically verify the effectiveness of the tuned mass damper device. The wind load time history is simulated based on Kaimal spectrum by the harmony superposition method. The equations of motion of a system with tuned mass damper under wind load excitation are proposed, and the schematic of tuned mass damper is introduced. The effects of mass ratio, frequency ratio, damping ratio, the change of the sag of transmission line, and the robustness of TMD are investigated, respectively. Results show that (1) the change of mass ratio has a greater effect on the vibration reduction ratio than those of frequency ratio and damping ratio, and the best vibration reduction ratio of TMD is not the frequency ratio of 1; (2) the sag-span ratio has an insignificant effect on the vibration reduction ratio of transmission tower when the change of sag-span ratio is not large; and (3) the effect of ice should be considered when the robustness study of TMD is carried out.